Uso de isótopos estáveis na determinação de impactos por enriquecimento orgânico em um estuário tropical - Varzim, Cíntia da Silva (2017)
Estuaries are important transitional ecosystems between land and sea, with high biological productivity and are vital for the adjacent coastal areas. They are under intense human pressure, mainly urban and industrial, due to the dumping of untreated effluents with impacts on the ecosystem. Considering the wide quantity of sewage released in these ecosystems and the necessity of monitoring the effects of these impacts, it is important to use different methods to determine the presence of pollutants and their effects on the estuarine food chain. We evaluated the organic enrichment impact on the benthic food web in Vitória Bay estuarine complex, Vitória, Espírito Santo, Brazil. We used stable isotopes (d13C and d15N) from benthic macrofauna, with geochemical markers as coprostanol and epicoprostanol and their ratio, to validate isotopic analysis results. The macrofaunal nitrogen isotopic signatures at contaminated sites were enriched when compared to the noncontaminated. Macrofaunal trophic niche amplitude at most contaminated sites was smaller if compared to the non-contaminated sites. Our results suggest that stable isotopic signatures from benthic macrofauna could be used to evidence environmental impacts from organic enrichment at tropical estuaries under heavily polluted conditions.